Evaluation of a downstream process for the recovery and concentration of a Cell-Culture-Derived rVSV-Spike COVID-19 vaccine candidate. Issue 48 (26th November 2021) - Makovitzki, Arik; Lerer, Elad; Kafri, Yaron; Adar, Yaakov; Cherry, Lilach; Lupu, Edith; Monash, Arik; Levy, Rona; Israeli, Ofir; Dor, Eyal; Epstein, Eyal; Levin, Lilach; et al.
Abstract: rVSV-Spike (rVSV-S) is a recombinant viral vaccine candidate under development to control the COVID-19 pandemic and is currently in phase II clinical trials. rVSV-S induces neutralizing antibodies and protects against SARS-CoV-2 infection in animal models. Bringing rVSV-S to clinical trials required the development of a scalable downstream process for the production of rVSV-S that can meet regulatory guidelines. The objective of this study was the development of the first downstream unit operations for cell-culture-derived rVSV-S, namely, the removal of nucleic acid contamination, the clarification and concentration of viral harvested supernatant, and buffer exchange. Retaining the infectivity of the rVSV-S during the downstream process was challenged by the shear sensitivity of the enveloped rVSV-S and its membrane protruding spike protein. Through a series of screening experiments, we evaluated and established the required endonuclease treatment conditions, filter train composition, and hollow fiber-tangential flow filtration parameters to remove large particles, reduce the load of impurities, and concentrate and exchange the buffer while retaining rVSV-S infectivity. The combined effect of the first unit operations on viral recovery and the removal of critical impurities was examined during scale-up experiments. Overall, approximately 40% of viral recovery was obtained and the regulatory requirements of less than 10 ng host cell DNA per dose were met. However, while 86–97% of the host cell proteins were removed, the regulatory acceptable HCP levels were not achieved, requiring subsequent purification and polishing steps. The results we obtained during the scale-up experiments were similar to those obtained during the screening experiments, indicating the scalability of the process. The findings of this study set the foundation for the development of a complete downstream manufacturing process, requiring subsequent purification and polishing unit operations for clinical preparations of rVSV-S.